Immune cell composition in normal human kidneys - Park, Jun-Gyu; Na, Myeongsu; Kim, Min-Gang; Park, Su Hwan; Lee, Hack June; Kim, Dong Ki; Kwak, Cheol; Kim, Yon Su; Chang, Sunghoe; Moon, Kyung Chul; Lee, Dong-Sup; Han, Seung Seok (Scientific reports, 2020)
An understanding of immunological mechanisms in kidney diseases has advanced using mouse kidneys. However, the profiling of immune cell subsets in human kidneys remains undetermined, particularly compared with mouse kidneys. Normal human kidneys were obtained from radically nephrectomised patients with urogenital malignancy (n = 15). Subsequently, human kidney immune cell subsets were analysed using multicolor flow cytometry and compared with subsets from C57BL/6 or BALB/c mice under specific pathogen-free conditions. Twenty kidney sections from healthy kidney donors or subjects without specific renal lesions were additionally analysed by immunohistochemistry. In human kidneys, 47% ± 12% (maximum 63%) of immune cells were CD3 + T cells. Kidney CD4 + and CD8 + T cells comprised 44% and 56% of total T cells. Of these, 47% ± 15% of T cells displayed an effector memory phenotype (CCR7 − CD45RA − CD69 − ), and 48% ± 19% were kidney-resident cells (CCR7 − CD45RA − CD69 + ). However, the proportions of human CD14 + and CD16 + myeloid cells were approximately 10% of total immune cells. A predominance of CD3 + T cells and a low proportion of CD14 + or CD68 + myeloid cells were also identified in healthy human kidney sections. In mouse kidneys, kidney-resident macrophages (CD11b low F4/80 high ) were the most predominant subset (up to 50%) but the proportion of CD3 + T cells was less than 20%. These results will be of use in studies in which mouse results are translated into human cases under homeostatic conditions or with disease.